Evidence of non-Plasmodium falciparum malaria infection in Kédougou, Sénégal. (December 2017) - Daniels, Rachel; Deme, Awa; Gomis, Jules; Dieye, Baba; Durfee, Katelyn; Thwing, Julie; Fall, Fatou; Ba, Mady; Ndiop, Medoune; Badiane, Aida; Ndiaye, Yaye; Wirth, Dyann; et al.
Abstract Background Expanded malaria control efforts in Sénégal have resulted in increased use of rapid diagnostic tests (RDT) to identify the primary disease-causingPlasmodium species, Plasmodium falciparum . However, the type of RDT utilized in Sénégal does not detect other malaria-causing species such asPlasmodium ovale spp., Plasmodium malariae, orPlasmodium vivax . Consequently, there is a lack of information about the frequency and types of malaria infections occurring in Sénégal. This study set out to better determine whether species other thanP. falciparum were evident among patients evaluated for possible malaria infection in Kédougou, Sénégal. Methods Real-time polymerase chain reaction speciation assays forP. vivax, P. ovale spp., andP. malariae were developed and validated by sequencing and DNA extracted from 475Plasmodium falciparum -specific HRP2-based RDT collected between 2013 and 2014 from a facility-based sample of symptomatic patients from two health clinics in Kédougou, a hyper-endemic region in southeastern Sénégal, were analysed. Results Plasmodium malariae (n = 3) andP. ovale wallikeri (n = 2) were observed as co-infections withP. falciparum among patients with positive RDT results (n = 187), including one patient positive for all three species. Among 288 negative RDT samples, samples positive forP. falciparum (n = 24), P. ovale curtisi (n = 3), P. ovale wallikeri (n = 1), andP. malariae (n = 3) were identified, corresponding to a non-falciparum positivity rate of 2.5%. Conclusions These findings emphasize the limitations of the RDT used for malaria diagnosis and demonstrate that non-P. falciparum malaria infections occur in Sénégal. Current RDT used for routine clinical diagnosis do not necessarily provide an accurate reflection of malaria transmission in Kédougou, Sénégal, and more sensitive and specific methods are required for diagnosis and patient care, as well as surveillance and elimination activities. These findings have implications for other malaria endemic settings where species besidesP. falciparum may be transmitted and overlooked by control or elimination activities.